2020
DOI: 10.1021/acsbiomaterials.9b01480
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2-carboxyethyl)phosphine-Mediated Nanometric Extracellular Matrix-Coating Method of Mesenchymal Stem Cells

Abstract: Human iPSC-derived mesenchymal stem cells (iMSCs) are an alternative to primary mesenchymal stem cells (MSCs), which have been a limited supply, and have attracted a great deal of interest as a promising cell source in cell-based therapy. However, despite their enormous therapeutic potential, it has been difficult to translate this potential into clinical applications due to the short viability duration of transplanted iMSCs. Therefore, to maximize the therapeutic effects of iMSCs, it is extremely important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Adapted with permission. [ 193 ] Copyright 2020, The American Chemical Society. c) (Left) Schematic for formation of GLN‐hydrogel shells on individual MSCs.…”
Section: Demonstrated Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted with permission. [ 193 ] Copyright 2020, The American Chemical Society. c) (Left) Schematic for formation of GLN‐hydrogel shells on individual MSCs.…”
Section: Demonstrated Applicationsmentioning
confidence: 99%
“…[191,192] Such drawbacks can be overcome by coating individual cells with ECM-mimetic materials prior to spheroid formation. For example, MSCs, derived from human iPSCs, were coated with collagen type I or decellularized bone ECMs (Figure 10b), [193] after mild TCEP treatment to expose free thiols at the membranes, which apparently enhanced the adsorption of ECM components onto the cell surfaces. [194] MSC@ECM showed the enhanced viability after the formation [193] Copyright 2020, The American Chemical Society.…”
Section: Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Kim and co‐workers found that the TCEP treatment on U87 and U251 glioma cells promoted the cellular anchorage to the ECM, thus enhancing cell adhesion. [ 79,80 ] The TCEP treatment also increased the expression level of focal adhesion complex‐related proteins, such as vinculin and an activated form of FAK. Due to these advantages, the coating efficiency of decellularized bone ECM materials for individual human‐induced pluripotent stem cells (iPSCs) was significantly enhanced, as well as for 3D cell spheroids.…”
Section: Materials and Strategies For Mammalian‐cell Nanocoatingmentioning
confidence: 99%
“…However, despite these merits, some limitations exist for its clinical application. On one hand, TCEP has safety concerns, such as toxicity at concentrations over 1 × 10 –2 M, making it unsuitable for the direct administration on organisms. , On the other hand, TCEP disrupts mucus strands, thus inhibiting the mucociliary transport of large particles . Therefore, the development of alternative biocompatible and effective mucolytic agents is of great significance in the treatment of airway obstruction diseases.…”
Section: Introductionmentioning
confidence: 99%